The complete mitochondrial genome of bullet tuna (Auxis rochei) from South China Sea - Lei Xu; Xuehui Wang; Feiyan Du (Mitochondrial DNA. Part B. Resources, 2019)
Auxis rochei is one of genus Auxis and widely distributed in tropical and subtropical waters. In this study, we described the complete mitochondrial genome of A. rochei. The genome is 16505 bp in length, encoding the standard set of 13 protein-coding genes, 21 transfer RNA genes, two ribosomal RNA genes, and a non-coding D-loop, with circular organization. The overall base composition of the whole mitochondrial genome was A (27.92%), T (25.01%), G (17.09%), and C (29.98%) with an AT bias of 52.94%. The longest protein-coding genes of these species was ND5, whereas the shortest ATP8.